Novel Insights Into the Sulfated Glucuronic Acid-Based Anti-SARS-CoV-2 Mechanism of Exopolysaccharides From Halophilic Archaeon Haloarcula hispanica - Xu, Yueqiang; Li, Yan; You, Xin; Pei, Caixia; Wang, Zhuo; Jiao, Siming; Zhao, Xin; Lin, Xuan; Lü, Yang; Jin, Cheng; Gao, George Fu; Li, Jianjun; et al. (Frontiers in Chemistry, 2022)
The pandemic caused by SARS-CoV-2 is the most widely spread disease in the 21st century. Due to the continuous emergence of variants across the world, it is necessary to expand our understanding of host–virus interactions and explore new agents against SARS-CoV-2. In this study, it was found exopolysaccharides (EPSs) from halophilic archaeon Haloarcula hispanica ATCC33960 can bind to the spike protein of SARS-CoV-2 with the binding constant KD of 2.23 nM, block the binding of spike protein to Vero E6 and bronchial epithelial BEAS-2B cells, and inhibit pseudovirus infection. However, EPSs from the gene deletion mutant △HAH_1206 almost completely lost the antiviral activity against SARS-CoV-2. A significant reduction of glucuronic acid (GlcA) and the sulfation level in EPSs of △HAH_1206 was clearly observed. Our results indicated that sulfated GlcA in EPSs is possible for a main structural unit in their inhibition of binding of SARS-CoV-2 to host cells, which would provide a novel antiviral mechanism and a guide for designing new agents against SARS-CoV-2.